Development of Large Chain Wear Running-in Test-bed and Its Measurement and Control System - Liu Qiang; Zhou Lianquan; He Zhenzhi; Han Jiguang; Bo Xiaonan (Jixie chuandong)
In order to test the durability， service life and other properties of roller chain， based on the principle of closed power flow， an automatic test-bed is designed for testing the wear running-in of roller chain. To enable the power flow closure of the test system， the tension and clamping device is controlled by computer and the sprocket staggered teeth method is used for loading torque to the test chain and the accompanying test chain. The hydraulic and computer control systems are designed to realize the automatic tension and clamping function of the test-bed. The design and selection of tensioning cylinder and clamping cylinder are also carried out， so that the test-bed can meet the test conditions of different types of chains. The prototype test-bed is built by processing and purchasing required components. The wear running-in test of the roller chain is carried out by using the prototype. The results show that the prototype can meet the test conditions of different types of roller chains with low energy consumption and reliable operation.